2022
DOI: 10.1002/pros.24468
|View full text |Cite
|
Sign up to set email alerts
|

Prostate fibroblasts enhance androgen receptor splice variant 7 expression in prostate cancer cells

Abstract: Background: Androgen receptor splice variant (AR-V) expression has been associated with prostate cancer (PCa) progression to castration-resistant PCa during androgen deprivation therapy, which reduces androgen production and inhibits androgen action in PCa cells. However, the mechanisms whereby aberrant AR-V expression is increased in PCa are still largely unknown. Fibroblasts in tumor stroma influence PCa initiation and aggressiveness, and which may play a crucial role in eliciting genetic changes during mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The results of RT-qPCR assays ( Figure 4 C) indicated that only LNCaP and 22Rv1 cells express measurable ARFL and ARv7 mRNA instead of PZ-HPV-7, CA-HPV-10, PC-3, and DU145 cells; moreover, 22Rv1 cells express endogenously abundant ARv7. These results are in agreement with previous reports [ 43 , 47 , 48 ]. Both ectopic overexpressed-ARv7 22Rv1 and PC-3 cells induced NDRG1 expression compared to mock-transfected 22Rv1 and PC-3 cells, respectively; in addition, the ectopic overexpression of ARv7 induced PSA expression in 22Rv1 cells under androgen ablation conditions ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 94%
“…The results of RT-qPCR assays ( Figure 4 C) indicated that only LNCaP and 22Rv1 cells express measurable ARFL and ARv7 mRNA instead of PZ-HPV-7, CA-HPV-10, PC-3, and DU145 cells; moreover, 22Rv1 cells express endogenously abundant ARv7. These results are in agreement with previous reports [ 43 , 47 , 48 ]. Both ectopic overexpressed-ARv7 22Rv1 and PC-3 cells induced NDRG1 expression compared to mock-transfected 22Rv1 and PC-3 cells, respectively; in addition, the ectopic overexpression of ARv7 induced PSA expression in 22Rv1 cells under androgen ablation conditions ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 94%